How pupil and teacher perceptions of misbehaviour vary in an Irish primary school classroom: A case study - O'Meara, Megan (Trinity College (Dublin, Ireland). School of Education, 2021)
This research aimed to explore the contrast in pupil and teacher perceptions of misbehaviour in an Irish primary school classroom. The researcher had experienced challenging behaviour throughout her teaching career and aimed to examine how a pupil’s perception of their behaviour could influence teaching and learning in the classroom. There is a range of literature that explores teacher perceptions of misbehaviour, but research on pupil perceptions are less common, with only a few studies completed. The research hoped to examine how pupil and teacher perceptions differ when focusing on misbehaviour in the classroom. It hoped to explore the impact of such contrasting perspectives on teaching and learning. This research adopted a mixed methods approach, incorporating both quantitative and qualitative data within a case study. A case study involves the investigation and analysis of a specific situation (Newby, 2010) and communicates the reality explored by the researcher and offers a sense of understanding and clarity to the reader (Cohen, Manion, & Morrison, 2007). This research used a pupil questionnaire to explore pupil perceptions of misbehaviours in the classroom, while teacher observations and reflection notes and a teacher tally chart were used to collect data from the perspective of the teacher. The findings of this research suggested that there was a contrast in the perceptions of teachers and pupils in regards misbehaviour in the classroom. There were two major findings that suggested the reasons for these contrasting perceptions of misbehaviour. The first finding suggested that pupils’ perceptions of misbehaviour differed in regards the perceived severity of various misbehaviours. The second finding suggested that pupils often found certain school rules confusing, and this lack of understanding could prove challenging for both pupils and teachers as pupils are often unaware, they are participating in such misbehaviours. These findings highlighted the contrast in pupil and teacher perspectives on misbehaviours.
Keywords: Positive Behaviour Management; Education